INVENTARISASI MAKROALGA DI PULAU PISANG PESISIR BARAT UNTUK PENYUSUNAN POSTER - Ervina Agustin; Widya Sartika Sulistiani; Rasuane Noor (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
Macroalgae is one component of the ecosystem that has an important role inwaters, especially on the coast of Pisang Island. The role of macroalgae formarine biota such as being a breeding ground and providing food. The PisangIsland Government plans that Pisang Island become one of the natural touristdestinations. Surely the region will experience a transition into a touristattraction and will have an influence on the ecosystem at sea. So before thetransition occurs, macroalgae research needs to be held on Pisang Island. Aqualitative descriptive research method with a purposive sampling techniqueusing a combination of transect lines. The data obtained were analyzed withShannon Winner.The objectives of the study of macroalgae on Pisang Island are: (1)Determine the species of macroalgae in Pisang Islands. (2) Knowing the resultsof research can be used as a poster. The results of macroalgae research onPisang Island found 10 species grouped into 3 divisions named Chaetomorphacrassa, Boergesenia forbesii, Avrainvillea erecta, Valonia aegagrophillia, Ulvalactuca, Sargassum polycytum, Turbinaria ornate, Fucus sp, Padina australis,Valonia aegagrophillia, Ulva lactuca, Sargassum polycytum, Turbinariaornate, Fucus sp. The results of the study were made into posters that can beused in learning and for the public. Posters contain information such asclassification of macroalgae, morphology, habitat benefits and there areoriginal photographs of macroalgae found. The results of poster validation,from material experts and design experts get a percentage of 96% with thecriteria